2007
DOI: 10.1177/0163443707081695
|View full text |Cite
|
Sign up to set email alerts
|

`The pillar of fire by night, to shew them light': Israeli broadcasting, the Supreme Court and the Zionist narrative

Abstract: This article discusses cases in which the Israeli Supreme Court was asked to block the broadcasting of television programs produced by the national broadcaster – the Israel Broadcasting Authority (IBA) – on the grounds that they purportedly misrepresented historical truths. The article shows, through various examples, how the court uses its ideological biases in order to serve the dominant interpretation of the history of Zionism and to perpetuate this interpretation by providing it with a judicial stamp of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The Biton Committee’s most celebrated recommendation was to produce a new documentary series: The Mizrahi Pillar of Fire . The original Pillar of Fire , produced by the Israel Broadcasting Authority (IBA) in the early 1980s, is a well-known documentary series comprising 19 episodes that portrays the history of Zionism while ignoring the Mizrahi narrative (Schejter, 2007). This oversight has been an open wound for the Mizrahi community ever since, especially after the Israeli Supreme Court’s 1981 rejection of their petition to block the broadcast of the series until it was amended to reflect a ‘balanced’ version of history (Schejter, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Biton Committee’s most celebrated recommendation was to produce a new documentary series: The Mizrahi Pillar of Fire . The original Pillar of Fire , produced by the Israel Broadcasting Authority (IBA) in the early 1980s, is a well-known documentary series comprising 19 episodes that portrays the history of Zionism while ignoring the Mizrahi narrative (Schejter, 2007). This oversight has been an open wound for the Mizrahi community ever since, especially after the Israeli Supreme Court’s 1981 rejection of their petition to block the broadcast of the series until it was amended to reflect a ‘balanced’ version of history (Schejter, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study conducted by the Israel Central Bureau of Statistics, Jews of ‘Asian-African’ background are less likely than Israelis of European origin to earn an academic degree (Dobrin, 2015: 37). Other studies have shown that Mizrahi Jews predominate in Israel’s development towns, located at the geographical and social periphery (Schejter, 2007), and that Mizrahi Jews earn less than their Ashkenazi counterparts (Swirski et al, 2015).…”
Section: The Mizrahi Struggle In Israel and The Biton Committeementioning
confidence: 99%
See 1 more Smart Citation
“…This has been addressed by communications scholars in cases where such challenges are quite obvious – such as the cases of Ireland (e.g. Barbrook, 1992; Watson, 2002) and Israel (Jamal, 2007; Schejter, 2007). Since identity challenges are intensified in the specific context of Third World states, popular culture products like television are of even greater political importance there, as Katz and Wedell elaborate in their work.…”
Section: Using Popular Culture To Manage Ontological Security Challengesmentioning
confidence: 99%
“…Hannah's narrative maneuvers between the hegemonic Zionist story of redeeming the ignorant immigrants, teaching them the basics of modern life, and the Mizrahi counternarrative of prejudice against the non-European immigrants, of forced assimilation that planned to eradicate all traditional values in exchange for tokens of modernity, e.g., literacy (Schejter, 2007;Goldberg, Porat & Schwarz, 2006). 7 Nevertheless, the story told by Hannah and other women is multilayered -they accepted some things while rejecting others.…”
Section: Narrative Of the Third Space -Between Hegemony And Counternamentioning
confidence: 99%